STRATEGI MAHASISWA PROFESI NERS DALAM MENGHADAPI UJI KOMPETENSI NERS DI USM INDONESIA - Henny Syapitri; Johansen Hutajulu (LPPM STIKES Muhammadiyah Kendal, 2020)
The emergence of the nursing higher education system in Indonesia is expected to produce graduates who have the attitudes, knowledge and professional skills of nursing so that they are able to carry out their role in providing nursing services. The Indonesian government has implemented a higher education quality assurance system in the health sector, including a competency test. Competency test is a person's ability that can be observed which includes knowledge, skills and attitudes in completing a job or task with a set performance performance standard. According to data from the Association of Indonesian Nurse Education Institutions (AIPNI), the average UKOM Nurse graduation in October 2018 only reached 35.3%. Data from the Sari Mutiara Indonesia University, the pass rate for the 2018 Nurse Competency Test actually increased by 82%. Based on these data, it is necessary to identify student preparation in facing competency tests. The purpose of this study was to identify the strategies of the Nurse Profession students in facing the Nurse Competency Test. This type of research is descriptive research. The population in this study were students of the Nurse Profession at Sari Mutiara Indonesia University. The sample in this study were 72 people using the total population technique. The instrument used in this study was a questionnaire that was created and tested by the researchers themselves. The validity test was carried out in different places, the results of validity and reliability were tested with the correlation between Pearson Product Moment and Cronbach's alpha, with a Cronbach Alpha value greater than 0.721. The data analysis used was univariate analysis. The results showed that the majority of students had a reference, namely (88.9%), the majority of students understood the blueprint of the questions well, which was (77.8%), all students (100%) attended intensive tutoring at campus and online tutoring, students (100%) participate in local and national tryouts. Nurse education institutions have a big responsibility in supporting the graduation of students from UKOM. So that the institution is expected to provide guidance to students in order to increase the graduation rate of UKOM and improve the quality of graduates.